Empowering interventions to promote sustainable lifestyles: Testing the habit discontinuity hypothesis in a field experiment. (March 2016) - Verplanken, Bas; Roy, Deborah
Abstract: This study tested the habit discontinuity hypothesis, which states that behaviour change interventions are more effective when delivered in the context of life course changes. The assumption was that when habits are (temporarily) disturbed, people are more sensitive to new information and adopt a mind-set that is conducive to behaviour change. A field experiment was conducted among 800 participants, who received either an intervention promoting sustainable behaviours, or were in a no-intervention control condition. In both conditions half of the households had recently relocated, and were matched with households that had not relocated. Self-reported frequencies of twenty-five environment-related behaviours were assessed at baseline and eight weeks later. While controlling for past behaviour, habit strength, intentions, perceived control, biospheric values, personal norms, and personal involvement, the intervention was more effective among recently relocated participants. The results suggested that the duration of the 'window of opportunity' was three months after relocation. Highlights: Life course changes disrupt old habits and may create a mood for more change. An intervention to promote sustainable behaviours was tested among 800 households. Behaviour change was more likely if participants recently had moved house. The results were compared with non-movers and a no-intervention control group. The 'window of opportunity' lasted up to three months after relocation.